(untitled) (Praxis Educativa, 2026)
The aim of this article is to describe the reactions of secondary school teachers and students to discourses that exalt supposed freedom, individualism, and competition in contemporary society. The central hypothesis we seek to develop is that, within the school setting, individuals critically engage with logics that promote self-management, survival of the fittest, and meritocracy as regimes of truth (Foucault, 1979), particularly in times and contexts where inequalities are deepening and intensifying. At the same time, these individuals envision alternative ways of living together, grounded in the notion that "no one is saved alone," where solidarity and camaraderie become central. To explore this, we designed a multi-method approach that includes audiovisual productions and in-depth interviews with both teachers and students. The findings reveal that situations of insecurity, poverty, economic crisis, death, suffering, cruelty, and selfishness do not prevent individuals in school contexts from empathizing with others and recognizing the need to both support and be supported by one another. They highlight the importance of solidarity, empathy, coexistence, and teamwork as fundamental to building a shared life in society